THE INFLUENCE OF THE BIG FIVE PERSONALITY TRAITS ON MEDICAL SKILL EXAMINATION RESULTS: A STUDY ON MEDICAL STUDENTS AT HANOI MEDICAL UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objectives: This study aimed to investigate the association between medical students’ personality traits and their performance in preclinical practical examinations conducted using the objective structured clinical examination (OSCE) format.Method: A cross-sectional descriptive study was conducted on 1011 second- and third-year medical students at Hanoi Medical University. Personality traits were assessed using the TIPI. Data were analyzed using independent samples T-tests and multivariable linear regression modeling.Results: The mean OSCE score for female students (8.04 ± 0.57) was significantly higher than that for male students (7.79 ± 0.67) with p < 0.01. Second-year students achieved higher scores than third-year students (8.09 ± 0.63 vs. 7.71 ± 0.60; p < 0.01). Extraversion and Conscientiousness were identified as two personality traits independently associated with an increase in OSCE scores. Conversely, male gender and enrollment in the third academic year were associated with a decrease in scores.Conclusion: Student personality traits are significantly correlated with practical competency. Students exhibiting high Conscientiousness and Extraversion possess a distinct advantage in the OSCE setting. The notable difficulty experienced by third-year students, particularly in stations focusing on interpretation and diagnostic reasoning, suggests challenges during the transition phase toward clinical practice. These findings provide a valuable foundation for developing tailored teaching strategies to support medical students in enhancing their practical skills.
Keywords: Personality traits, medical skills, OSCE, medical students, multivariate regression.